Gene networks associated with non-syndromic intellectual disability. (2nd January 2018) - Lee, Soohyun; Rudd, Stephen; Gratten, Jacob; Visscher, Peter M.; Prins, Johannes B.; Dawson, Paul A.
Abstract: Non-syndromic intellectual disability (NS-ID) is a genetically heterogeneous disorder, with more than 200 candidate genes to date. Despite the increasing number of novel mutations detected, a relatively low number of recurrently mutated genes have been identified, highlighting the complex genetic architecture of the disorder. A systematic search of PubMed and Medline identified 245 genes harbouring non-synonymous variants, insertions or deletions, which were identified as candidate NS-ID genes from case reports or from linkage or pedigree analyses. From this list, 33 genes are common to syndromic intellectual disability (S-ID) and 58 genes are common to certain neurological and neuropsychiatric disorders that often include intellectual disability as a clinical feature. We examined the evolutionary constraint and brain expression of these gene sets, and we performed gene network and protein–protein interaction analyses using GeneGO MetaCore TM and DAPPLE, respectively. The 245 NS-ID candidate genes were over-represented in axon guidance, synaptogenesis, cell adhesion and neurotransmission pathways, all of which are key neurodevelopmental processes for the establishment of mature neuronal circuitry in the brain. These 245 genes exhibit significantly elevated expression in human brain and are evolutionarily constrained, consistent with expectations for a brain disorder such as NS-ID that is associated with reduced fecundity. In addition, we report enrichment of dopaminergic and glutamatergic pathways for those candidate NS-ID genes that are common to S-ID and/or neurological and neuropsychiatric disorders that exhibit intellectual disability. Collectively, this study provides an overview and analysis of gene networks associated with NS-ID and suggests modulation of neurotransmission, particularly dopaminergic and glutamatergic systems as key contributors to synaptic dysfunction in NS-ID.